Incorporation of carbopol to palm olein based analgesic cream: effect on formulation characteristics - Win, Thazin; Rajagopal, JeevanRaj; Mandal, Uttam Kumar; Sengupta, Pinaki; Chatterjee, Bappaditya (Latin American Journal of Pharmacy, 2017)
The purpose of the investigation was to incorporate carbopol gel with palm olein based emulsion and to investigate the effect of such incorporation on formulation characteristics. A palm olein based emulsion was formulated followed by addition of carbopol 940 to it. The critical parameters of incorporating carbopol in bench scale level were checked. The developed palm olein-carbopol based analgesic cream was analyzed for pH, zeta potential, viscosity, rheological property and forced centrifugation.Incorporation of 0.3% of carbopol gel (1% w/w) helps to maintain the viscosity and stability. pH and zeta potential of palm olein-carbopol combined cream was within range of 6.90 to 7.20 and -23.1 to -74.9, respectively. Combination of palm olein based emulsion and carbopol would be a suitable option for topical cream formulation. The pH of carbopol gel and method of mixing with the palm olein based emulsion had crucial effects on phase separation of the product.